2001
DOI: 10.1073/pnas.091110798
|View full text |Cite
|
Sign up to set email alerts
|

Changes in global gene expression patterns during development and maturation of the rat kidney

Abstract: We set out to define patterns of gene expression during kidney organogenesis by using high-density DNA array technology. Expression analysis of 8,740 rat genes revealed five discrete patterns or groups of gene expression during nephrogenesis. Group 1 consisted of genes with very high expression in the early embryonic kidney, many with roles in protein translation and DNA replication. Group 2 consisted of genes that peaked in midembryogenesis and contained many transcripts specifying proteins of the extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 26 publications
(26 reference statements)
11
120
0
1
Order By: Relevance
“…This supports the validity of using a pooled fetal kidney sample. Through comparison with a rat kidney development data set (Stuart et al, 2001), we found that 36 of 50 genes (72%) upregulated in Wilms tumors are more abundantly expressed in the early stages of kidney development. In contrast, 67 of 82 genes (82%) downregulated in Wilms tumors are preferentially expressed in the later stages of kidney development.…”
Section: Gene Expression Connection Between Wilms Tumorigenesis and Kmentioning
confidence: 99%
See 3 more Smart Citations
“…This supports the validity of using a pooled fetal kidney sample. Through comparison with a rat kidney development data set (Stuart et al, 2001), we found that 36 of 50 genes (72%) upregulated in Wilms tumors are more abundantly expressed in the early stages of kidney development. In contrast, 67 of 82 genes (82%) downregulated in Wilms tumors are preferentially expressed in the later stages of kidney development.…”
Section: Gene Expression Connection Between Wilms Tumorigenesis and Kmentioning
confidence: 99%
“…Notably, some genes in Category 2 (such as APOE and TIEG) and all genes in Category 3 have been classified as early or late nephrogenic genes by expression profiling (Stuart et al, 2001). Owing to the putative linkage of Wilms tumor to nephrogenesis, potential roles in normal kidney development for genes in these categories could be explored further.…”
Section: Wilms Tumor and Kidney Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen of the outliers from the microarray experiments have previously been implicated in kidney development in extensive expression profiling studies performed in mouse and rat by Schwab et al (2003) and Stuart et al (2001), respectively (e.g., midkine, Cxcl12, and Wnt-4). In addition, six other factors have been documented in the literature to be involved in kidney development, again providing independent verification of our data.…”
Section: Definition Of the Dynamic Secretome Of Early Metanephric Devmentioning
confidence: 99%